Experimental infection of high health pigs with porcine circovirus type 2 (PCV2) and Lawsonia intracellularis - Hansen, Mette S.; Jensen, Tim K.; Hjulsager, Charlotte K.; Angen, Øystein; Riber, Ulla; Nielsen, Jens; Heegaard, Peter M. H.; Larsen, Lars E. (Frontiers in Veterinary Science, 2022)
Background: Porcine circovirus type 2 (PCV2) and Lawsonia intracellularis infections can cause enteritis in pigs. A Danish study showed a significantly higher probability of detecting PCV2 without concurrent L. intracellularis infection, indicating that one of these pathogens has an impact on the dynamics of the other. Therefore, a delayed co-infection model was set up, initially aiming at investigating the interaction between PCV2 and L. intracellularis in pigs challenged with PCV2 and two weeks later with L. intracellularis. But due to PCV2 contamination of the L. intracellularis inoculum the aim was revisited to describing the infection dynamics and pathogenesis of pigs infected with PCV2 followed by delayed simultaneous exposure to PCV2 and L. intracellularis. Twenty-four high-health piglets were divided into three groups of 8 pigs (A, B, C) and inoculated at experimental day (EXD) 0 with mock (groups A and B) or PCV2 (group C), and at EXD 14 with mock (group A) or L. intracellularis/PCV2 (groups B and C). The pigs underwent clinical examination, and were necropsied at EXD 51-52. Furthermore, histology, immunohistochemistry, serology and PCR for PCV2 and L. intracellularis, and measurement of C-reactive protein were carried out. Results: Group A remained negative for PCV2 and L. intracellularis. Following inoculation with L. intracellularis/PCV2, no significant differences were observed between group B and C, however pigs already infected with PCV2 (group C) showed milder clinical signs and exhibited milder intestinal lesions, less shedding of L. intracellularis and developed higher L. intracellularis antibody titers than the pigs in group B that only received the combined infection. Though the differences between group B and C were non-significant, all results pointed in the same direction, indicating that the pigs in group B were more affected by the L. intracellularis infection compared to the pigs in group C. Conclusions: Previous exposure to PCV2 had limited impact on the subsequent exposure to a combined L. intracellularis/PCV2 inoculation. However, there was a tendency that the infection dynamics of PCV2 and development of antibodies to PCV2 and L. intracellularis were altered in pigs previously exposed to PCV2. These differences should be confirmed in further experimental trials.